Inclusion of palliative and end of life care in health strategies aimed at integrated care: a documentary analysis [version 2; peer review: 2 approved] - Chambers, Rachel L.; Pask, Sophie; Higginson, Irene J.; Barclay, Stephen; Murtagh, Fliss E.M.; Sleeman, Katherine E. (AMRC Open Research, 2023)
Background: In England, Integrated Care Systems have been established to improve integration of care, as part of the NHS Long Term Plan. For people near the end of life, palliative care can improve integration of care. We aimed to understand whether and how palliative and end of life care was included in Integrated Care System strategies, and to consider priorities for strengthening this. Methods: Documentary analysis of Integrated Care System (ICS) strategies, using summative content analysis, was performed. Google searches were used to identify NHS Trust, Clinical Commissioning Group or ICS websites. We searched these websites to identify strategies. Key terms were used to identify relevant content. Themes were mapped onto an adapted logic model for integrated care. Results: 23 Integrated Care System strategy documents were identified. Of these, two did not mention any of the key terms, and six highlighted palliative and end of life care as either a priority, area of focus, or an ambition. While most (19/23) strategies included elements that could be mapped onto the adapted logic model for integrated care, the thread from enablers and components, to structures, processes, outcomes, and impact was incomplete. Conclusions: Greater prioritisation of palliative and end of life care within recently established Integrated Care Systems could improve outcomes for people near the end of life, as well as reduce reliance on acute hospital care. Integrated Care Systems should consider involving patients, the public and palliative care stakeholders in the ongoing development of strategies. For strategies to be effective, our adapted logic model can be used to outline how different components of care fit together to achieve defined outcomes and impact.